Magnetic biocatalysts and their uses to obtain biodiesel and biosurfactants - López, Carmen; Cruz-Izquierdo, Álvaro; Picó, Enrique A.; García-Bárcena, Teresa; Villarroel, Noelia; Llama, María J.; Serra, Juan L. (Frontiers in Chemistry, 2014)
Nanobiocatalysis, as the synergistic combination of nanotechnology and biocatalysis, is rapidly emerging as a new frontier of biotechnology. The use of immobilized enzymes in industrial applications often presents advantages over their soluble counterparts, mainly in view of stability, reusability and simpler operational processing. Because of their singular properties, such as biocompatibility, large and modifiable surface and easy recovery, iron oxide magnetic nanoparticles (MNPs) are attractive super-paramagnetic materials that serve as a support for enzyme immobilization and facilitate separations by applying an external magnetic field. Cross-linked enzyme aggregates (CLEAs) have several benefits in the context of industrial applications since they can be cheaply and easily prepared from unpurified enzyme extracts and show improved storage and operational stability against denaturation by heat and organic solvents. In this work, by using the aforementioned advantages of MNPs of magnetite and CLEAs, we prepared two robust magnetically-separable types of nanobiocatalysts by binding either soluble enzyme onto the surface of MNPs functionalized with amino groups or by cross-linking aggregates of enzyme among them and to MNPs to obtain magnetic CLEAs. For this purpose the lipase B of Candida antarctica (CALB) was used. The hydrolytic and biosynthetic activities of the resulting magnetic nanobiocatalysts were assessed in aqueous and organic media. Thus, the hydrolysis of triglycerides and the transesterification reactions to synthesize biodiesel and biosurfactants were studied using magnetic CLEAs of CALB. The efficiency and easy performance of this magnetic biocatalysis validates this proof of concept and sets the basis for the application of magnetic CLEAs at industrial scale.